Strategi Pengelolaan Stres (Coping Stress) Berbasis Mindfulness dan Dukungan Kolaboratif untuk Meningkatkan Kesejahteraan Emosional Guru PAUD - Nayyiroh Nayyiroh (Global Education Journal, 2026)
Early Childhood Education (PAUD) teachers play a crucial and crucial role in the development of children's golden years. However, this profession is also highly susceptible to work stress due to several factors, including the administrative burden of schools, high demands for emotional regulation, and the diverse management of children's behavior in the classroom. This study aims to analyze the factors that trigger stress in PAUD teachers and the effectiveness of mindfulness-based stress management strategies and collaborative methods (co-teaching). Using a systematic literature review of reputable national journals (2020–2026), the analysis shows that poorly managed stress negatively impacts the quality of classroom management and educational interactions. Conversely, the application of emotional coping through regular mindfulness training and institutional approaches such as co-teaching has been shown to significantly reduce burnout levels and improve mental well-being for teachers on an ongoing basis.